Challenges of Family Collaboration with Schools in Online Learning - Esa Nur Wahyuni; Alfiana Yuli Efiyanti; Luthfiya Fathi Pusposari; Ananda Setiawan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Online learning during the pandemic provides awareness that education requires good collaboration between parents (family) and schools. In approximately two years, the application of learning from home became an important moment for strengthening family and school collaboration to carry out learning. This study aims to map the challenges faced by both the family and the school to collaborate, especially in the face of online learning. This research uses a qualitative approach. Data were obtained in 3 primary schools through interviews and observations with data sources of 30 parents, nine teachers, six school committees, and three principals. Data analysis using qualitative analysis. The results showed three problems that became challenges for collaboration between families and schools, including academic, social, and economic problems. These three challenges need to be solved by the commitment of schools and families to develop the welfare of children in schools